The Perceived Student’s Opinion On Post-Graduate Job Opportunities: Findings From Uin Ar-Raniry Islamic Communication And Broacasting Master Programme - Ridwan M. Hasan; Jailani; Jasafat (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2022)
This research is a descriptive study that examines the development of the Islamic Communication and Broadcasting Postgraduate Study Program and determines perceptions of the study program work opportunities for the alumni to become practitioners of political communication study fields, both in government and private sectors. The participants of this study were students from the 2016/2018 cohort. There are two main research questions of this study; How to revitalize job opportunities for study program postgraduate students to become a Political Communication Practitioners and how is the process of perceptions of interest in choosing postgraduate Islamic communication and broadcasting study programs at UIN Ar-Raniry Banda Aceh. In this study, researchers’ data collection is obtained through the use of a tracer study to track the performance and suggestions of graduates and graduate users so that clear indicators can be obtained about the number, future job profiles, and competencies required by the world of work.